Co-disposal of washery wastes at Jeebropilly colliery, Queensland, Australia - P. H. Williams; D. J. Morris (The Institute of Materials, Minerals and Mining, 1905)
The co-disposal of coarse and fine coal wastes by combined pumping through a pipeline to subaerial deposition was pioneered in Australia in 1990 by Jeebropilly colliery in Queensland. Significant segregation of fines is found to occur in its co-disposal delta, leading to the formation of distinct mainly coarse upper and fine-dominated lower segments; the upper delta drains rapidly and is able to support traffic on its surface immediately after deposition. An existing theory of subaerial deposition, originally developed for mine tailings alone and later extended to trial co-disposal, is shown to apply also to the upper segment of the full-scale Jeebropilly delta